The potential of biochar to mitigate soil acidification: a global meta-analysis - Nanhai Zhang; Jiamin Xing; Lianjun Wei; Chang Liu; Wenjing Zhao; Zihan Liu; Yuhao Wang; Enke Liu; Xiaolong Ren; Zhikuan Jia; Ting Wei; Kadambot H. M. Siddique; et al. (Biochar)
Abstract Soil acidification poses a significant challenge to soil health worldwide, and biochar emerges as a promising remedy. Nonetheless, a comprehensive evaluation of the impact of biochar on soil pH change is lacking, leaving considerable uncertainty regarding its efficacy across different environmental and management contexts. Here, we conducted a meta-analysis of 232 global studies to elucidate the impact of biochar on soil pH and identify key variables influencing its effectiveness. Our findings revealed that biochar application significantly increased soil pH by an average of 5.59%, but it decreased soil pH under certain circumstances. The raw material and pyrolysis temperature of biochar determine its pH. Furthermore, the biochar pH and initial soil pH modulate the magnitude of the biochar liming effect. High soil cation exchange capacity (CEC) values attenuate the biochar liming effect. When combined with organic nitrogen (N) fertilizer (6.95%), biochar increases soil pH more than when combined with inorganic N fertilizer (4.57%). Paddy fields exhibited a more pronounced response to biochar-induced pH elevation (5.98%) than dryland fields (3.75%), attributable to higher MAP, lower initial soil pH and soil CEC, higher biochar application rates and pH, and higher N fertilizer application. Overall, our meta-analysis underscores the lime-enhancing potential of biochar and the pivotal roles of MAP, biochar pH, initial soil pH, initial soil CEC, and farmland utilization mode in shaping its effectiveness. Graphical Abstract